Analysis of human factor H-related gene and protein expressed in rheumatoid arthritis synovium identifies a novel mechanism promoting dysregulated complement pathway activation - Nirmal K. Banda; Larry W. Moreland; Kevin D. Deane; Dmitri Simberg; Robert I. Scheinman; Rachel M. Frank; Jennifer A. Seifert; Accelerating Medicines Partnership (AMP) RA/SLE Network; Rachel Lau; Costantino Pitzalis; Myles J. Lewis; V. Michael Holers (Scientific Reports)
Abstract Factor H (FH) is a negative regulator of the alternative pathway (AP) of complement however, five human factor H-related (FHR) proteins, can also function ex vivo as positive regulators. We compare bulk FH and FHR mRNA expressions in both the human rheumatoid arthritis (RA) synovium and blood cells from the Pathobiology of Early Arthritis Cohort (PEAC) and the Stratification of biological therapies for Rheumatoid Arthritis by Pathobiology (STRAP) Cohort. FH and FHR proteins were detected using multiplexed immunohistochemistry (MIHC) in synovium. In three pathotypes, in the synovium, no differences were found in the expression of FHR mRNA. In the synovium, a significant negative correlation was observed between FH expression and the disease activity score and X-ray joint space narrowing. In RA patients, there was a significant positive correlation between FHR3 mRNA level, anti-cyclic citrullinated peptide (CCP) antibodies and rheumatoid factor (RF). FHR proteins were co-localized in the synovial lining area along with complement C3 while FH was almost undetectable in the synovial lining but abundant in sub-synovial lining areas. We do not know whether FH and FHR proteins are locally generated and deposited in synovium or come from circulation. In sum, due to the absence of FH but the presence of FHRs, the synovial lining might fail to be protected from complement-mediated attack, and FHR3 may play a particularly important pathogenic role.